Energy-exergy evaluation of liquefied hydrogen production system based on steam methane reforming and LNG revaporization - Qi Zhang; Xiaomei Huang; Shuhao Zhang; Yangxu Shen; Haidong Xu; Mengxiao Sun; Qingxin Wang; Liqian Zhao (Case Studies in Thermal Engineering, 2023)
The research motivation of this paper is to utilize the large amount of energy wasted during the LNG (liquefied natural gas) gasification process, and proposes a synergistic liquefied hydrogen (LH2) production and storage process scheme for LNG receiving station and methane reforming hydrogen production process - SMR-LNG combined liquefied hydrogen production system, which uses the cold energy from LNG to pre-cool the hydrogen and subsequently uses an expander to complete the liquefaction of hydrogen. The proposed process is modeled and simulated by Aspen HYSYS software, and its efficiency is evaluated and sensitivity analysis is carried out. The simulation results show that the system can produce liquefied hydrogen with a flow rate of 5.89 t/h with 99.99% purity when the LNG supply rate is 50 t/h. The power consumption of liquefied hydrogen is 46.6 kWh/kg LH2; meanwhile, the energy consumption of the HL subsystem is 15.9 kWh/kg LH2, lower than traditional value of 17∼19 kWh/kg LH2. The efficiency of the hydrogen production subsystem was 16.9%; the efficiency of the hydrogen liquefaction (HL) subsystem was 29.61%, which was significantly higher than the conventional industrial value of 21%; the overall energy efficiency (EE1) of the system was 56.52% with the exergy efficiency (EE2) of 22.2%, reflecting a relatively good thermodynamic perfection. The energy consumption of liquefied hydrogen per unit product is 98.71 GJ/kg LH2.